DEVELOPMENT AND SELF-DEVELOPMENT PARADIGM IN THE SCHOOL: REALITY OR VISION? - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2010)
The demand of national education reform was the transition from development to self-development paradigm after the independence of Lithuania. In the very first document which is related with school (i.e. Lithuanian SU school conception, 1988) school task that indicates human being as absolute value, was formulated in addition to this underlining concentration on physical and mental nature of a human being, conditions for individuality revelation, also provoking to seek personality supporting self-education and self-development. It was beneficial for positive external and internal assumption. These changes stated in the Lithuanian Education Law (1991) and Lithuanian Education Concept (1992). However the transition from development to self-development paradigm is under discussion till now. The aim of the article: to state the problem of the transition from development to self-development paradigm. The object: the problem of the transition from development to self-development paradigm. The methods: scientific literature review, research analyses, expert questionnaire.The article emphasizes external and internal assumption of change from development to self-development paradigm in the beginning of the independence of Lithuania and in the following five years. Also it stresses the positive influence on these assumptions as well as the essence of the problem.The article underlines various education research and its problematic aspects. Furthermore, it was identified by taking into consideration the research focused on the didactics competences of teachers and their role as well as expression in the didactic field that most of the teachers do not justify their activities according to self-development paradigm, and, in case, if they try to do it, only some fragment of it can be found.The result of the article author’s expert research made in 2009, represent the existence of the transition from development to self-development paradigm. Moreover, the article amplifies from the experts’ point of view the reason of these problems and possible solutions. Mainly it concentrates on problems of the teachers’ competence, also construction of the development content (national level) and its implementation (national and school level). In consequence, these problems are related with teachers’ education, qualification development, and the creation of the content development (didactics), also the management of the content development.
Keywords: the school; development; self-development paradigm; the reason of the transition; the possibilities of the solutions